2014
DOI: 10.1111/jsap.12220
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of persistent inguinal haemorrhage after prescrotal orchiectomy in a dog

Abstract: A one-year-old male Jack Russell terrier developed a prescrotal haematoma after elective orchiectomy. When surgical exploration failed to locate the responsible vessel and conservative therapy (applying a pressure bandage) was not successful in stabilising the dog, abdominal laparoscopy was performed. The haemorrhage originated from the spermatic cord in the inguinal canal bilaterally. After retracting the spermatic cord into the abdomen, haemostasis was performed using a vessel-sealing device. The prescrotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Articles on cryptorchidectomy described the incidental presence of testicular torsion (Birchard and Nappier 2008;Mayhew 2009) but specific description of emergency laparoscopy for acute abdominal pain has not been described in veterinary medicine. One article describes emergency laparoscopic exploration in a dog with persistent inguinal haemorrhage after prescrotal orchidectomy (Koenraadt et al 2014). The authors of this article found laparoscopy in the caudal abdomen to result in superior visibility due to the absence of intestines and also noted that the presence of the pelvis created adequate working space even with low intra-abdominal pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Articles on cryptorchidectomy described the incidental presence of testicular torsion (Birchard and Nappier 2008;Mayhew 2009) but specific description of emergency laparoscopy for acute abdominal pain has not been described in veterinary medicine. One article describes emergency laparoscopic exploration in a dog with persistent inguinal haemorrhage after prescrotal orchidectomy (Koenraadt et al 2014). The authors of this article found laparoscopy in the caudal abdomen to result in superior visibility due to the absence of intestines and also noted that the presence of the pelvis created adequate working space even with low intra-abdominal pressures.…”
Section: Discussionmentioning
confidence: 99%